Monitoring Democracy : When International Election Observation Works, and Why It Often Fails - Kelley, Judith G. (Book collections on Project MUSE., 2012)
In recent decades, governments and NGOs--in an effort to promote democracy, freedom, fairness, and stability throughout the world--have organized teams of observers to monitor elections in a variety of countries. But when more organizations join the practice without uniform standards, are assessments reliable? When politicians nonetheless cheat and monitors must return to countries even after two decades of engagement, what is accomplished? Monitoring Democracy argues that the practice of international election monitoring is broken, but still worth fixing. By analyzing the evolving interaction.